2016
DOI: 10.1016/j.jid.2016.05.095
|View full text |Cite
|
Sign up to set email alerts
|

RASopathy Gene Mutations in Melanoma

Abstract: Next-Generation sequencing (NGS) of melanomas has unraveled critical “driver” genes and genomic abnormalities, mostly defined as occurring at high frequency. In addition, less abundant mutations are present that link melanoma to a set of disorders, commonly called RASopathies. These disorders which include neurofibromatosis, Noonan and Legius syndromes, harbor germline mutations in various RAS/MAPK signaling pathway genes. We highlight shared amino acid substitutions between this set of RASopathy mutations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Interestingly, NF1 loss in melanoma is often associated with concurrent mutations in RASopathy genes 90,102 . These include RAS p21 protein activator 2 ( RASA2 ), PTPN11 , SOS1 , RAF1 , and SPRED1 , mutated in the germline of individuals with Noonan syndrome ( RASA2 , PTPN11 , SOS1 , RAF1 ), Noonan syndrome with multiple lentigines ( PTPN11 , RAF1 ), and Legius syndrome ( SPRED1 ) (Figure 1).…”
Section: Nf1 Mutations In Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, NF1 loss in melanoma is often associated with concurrent mutations in RASopathy genes 90,102 . These include RAS p21 protein activator 2 ( RASA2 ), PTPN11 , SOS1 , RAF1 , and SPRED1 , mutated in the germline of individuals with Noonan syndrome ( RASA2 , PTPN11 , SOS1 , RAF1 ), Noonan syndrome with multiple lentigines ( PTPN11 , RAF1 ), and Legius syndrome ( SPRED1 ) (Figure 1).…”
Section: Nf1 Mutations In Melanomamentioning
confidence: 99%
“…These include RAS p21 protein activator 2 ( RASA2 ), PTPN11 , SOS1 , RAF1 , and SPRED1 , mutated in the germline of individuals with Noonan syndrome ( RASA2 , PTPN11 , SOS1 , RAF1 ), Noonan syndrome with multiple lentigines ( PTPN11 , RAF1 ), and Legius syndrome ( SPRED1 ) (Figure 1). It is suggested that the co-occurring mutations may act synergistically in melanomas 102 .…”
Section: Nf1 Mutations In Melanomamentioning
confidence: 99%
“…As an example, patients with "RASopathies" (a group of rare genetic conditions such as cardiofaciocutaneous syndrome and Costello syndrome caused by mutations in genes of the RAS-RAF-MAPK pathway) have an increased risk of juvenile myelomonocytic leukemia, brain tumors, acute lymphoblastic leukemia, rhabdomyosarcoma, and neuroblastoma [55]. These patients do not, however, have increased risk of classic BRAF-mutated melanoma, although~75% of the cardiofaciocutaneous syndromes result from germline BRAF mutations [162], and pigmented nevi are very distinct in this syndrome and help to define it [163].…”
Section: Hereditary Conditions That Results From Germline Cancer-relatmentioning
confidence: 99%
“…The fetus was found to have a missense variant, c.622A>G (p.Ile208Val), in BRAF . Somatic variants in BRAF are well-documented in various cancers (Holderfield et al 2014; Halaban and Krauthammer 2016) and germline variants have been reported in individuals with RASopathies. Of note, at least nine BRAF missense variants have been observed in patients with Noonan syndrome, five of them de novo occurrences (Razzaque et al 2007; Nystrom et al 2008; Sarkozy et al 2009; Lee et al 2011; van Trier et al 2016).…”
Section: Case Presentationsmentioning
confidence: 99%